PENATALAKSANAAN FISIOTERAPI PADA DEQUERVAIN SYNDROME MENGGUNAKAN ULTRASOUND, TENS DAN TERAPI LATIHAN DI RSUD KRATON KAB. PEKALONGAN - Hendra Yusuf; Irine Dwitasari Wulandari (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
De Quervain syndrome is a painful problem which obtained by an inflammation at tendons on wrist area  exactly  at  the  thumb  area  (Ilyass,  2008).The  problems  that  will  occure  on  De  Quervain syndrome is pain, edema, spasm,  limitation  of ROM, decreased  muscle  strength and decreased of functional  ability.  The  examination  that  conducted  are  measurement  of  pain  with  VAS measurement of (Visual Analogue Scale), edema with anthropometry, Spasms by palpation, ROM with  gonemeter,  muscle  strength  by  MMT  (Manual  Muscle  Testing)  and  functional  ability  with ADL index (Activity Daily  Living). In this  case to solve the problems are with  Ultrasound (US),  Transcutaneous  Electrical  Nerve  Stimulation (TENS)  and  exercise  therapy,  after  conducted physiotherapy  management  as  much  as  six  times  obtained  results  among  decreased  of  pain, decreased of edema, decreased of spasm, increased ROM, increased muscle strength and increased of functional ability .Keywords :De Quervain syndrome, Ultrasound, TENS, Aktive movement